2021
DOI: 10.7717/peerj-cs.392
|View full text |Cite
|
Sign up to set email alerts
|

Towards suitable description of reference architectures

Abstract: Due to the increasing size and complexity of many current software systems, the architectural design of these systems has become a considerately complicated task. In this scenario, reference architectures have already proven to be very relevant to support the architectural design of systems in diverse critical application domains, such as health, avionics, transportation, and the automotive sector. However, these architectures are described in many different approaches, such as using textual description, infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It also includes guidelines and best practices for security, scalability, performance, portability, interoperability, and management [45]. Furthermore, Valle et al [46] revealed that existing works did not explicitly propose techniques (e.g. : models, procedures, or other terminology) to characterize interoperability in reference architectures.…”
Section: Frameworkmentioning
confidence: 99%
“…It also includes guidelines and best practices for security, scalability, performance, portability, interoperability, and management [45]. Furthermore, Valle et al [46] revealed that existing works did not explicitly propose techniques (e.g. : models, procedures, or other terminology) to characterize interoperability in reference architectures.…”
Section: Frameworkmentioning
confidence: 99%